Liana effects on tree functional groups and carbon balance in a lowland tropical forest, Panama and an analysis of progress in remote sensing of lianas - Proctor, Ashley David Caunt (2022)
1. Lianas (or vines) are woody climbers that root in the ground and utilise the structure of neighbouring trees to ascend into the forest canopy. These plant forms are found in forests globally, although they are particularly prevalent seasonal and lowland forests of the neotropics where they make up a significant proportion of woody species and stems. Lianas infest host trees and can dominate forest canopies, often described as structural parasites, lianas compete intensely with trees for sunlight and belowground resources without investing in their own supporting structure. 2. Research interest in lianas has increased substantially in recent decades, though they remain understudied compared to other plant forms. Chapter 1 reviews the increasingly comprehensive and geographically broad evidence base documenting the competitive effect of lianas upon host trees. Liana infestation has a significant and detrimental impact on tree growth, mortality, reproduction, and regeneration. Ultimately this reduces the capacity of trees to sequester and store carbon, a globally important ecosystem service provided by tropical forests. Furthermore, some evidence suggests that lianas are disproportionately affecting shade-tolerant carbon dense tree genera, contributing to a decline in these species. Reports of increasing liana abundance in the neotropics adds to the urgency for further research into the extent, magnitude, and mechanisms by which lianas effect the carbon balance in tropical forests. 3. Studying tropical forest canopies is challenging, as such relatively little is known about the distribution of lianas in forest canopies. Remote sensing is an emerging research method that has overcome some of the shortfalls associated with standard field surveys and can provide new and critical insights into liana ecology. Chapter 2 provides the first systematic assessment of the progress in the use of remote sensing to further understand the (i) spatial and temporal distributions, (ii) structure and biomass, (iii) responses to environmental conditions, and (iv) diversity, of lianas. The possibilities offered by new and future advances in remote sensing technology to study lianas, and the further data requirements needed, are then considered. For unanswered research questions to be resolved, liana ecology needs remote sensing. 4. Chapter 3 is the first study to report findings from a large-scale liana removal experiment for which there is more than 3-4 years of data. I consider eight census years of data from an ongoing liana-removal experiment in Gigante, Panama to address the paucity of research into how lianas impact carbon accumulation in trees with differing life histories and functional traits. Tree biomass growth was 49.21% lower in liana-infested plots over the eight-year period. This is attributed to a growth release in low wood density pioneer species in the four years after removal, which shifts towards high wood density shade tolerant species dominating growth contributions to overall forest carbon in the latter four census years. My findings also support the notion that severity of crown infestation dictates the magnitude of liana effect on tree biomass growth. This study highlights the need to quantify the contribution of species functional groups to forest carbon balance in order to better understand potential future liana effects. With reports of increasing liana abundance, my findings present a worrying picture of the resilience of tropical forests to persist as a functioning global carbon sink. 5. Synthesis. Our understanding of liana ecology and the relationship between these plant forms and carbon balance in tropical forests has increased rapidly. Observational studies, removal experiments, repeated plot censuses and the rapidly evolving applications of remote sensing have provided new insights into the nature of lianas and their interactions with the tropical forests they infest. This study adds to these foundations for future liana research by presenting a thorough review of existing literature, a critical analysis of the integration of remote sensing and an assessment of disproportionate lianas effects on tree functional groups. With the current state of tropical forest decline, urgent knowledge gaps must be addressed now more than ever.